Street Clown Phenomenon: Contradictory Presence of Beggars Dressed In Character Costumes In Banjarmasin City - Mochamad Dicky Aldi Saputra; Dimas Asto Aji An'Amta (International Journal of Politic, Public Policy and Environmental Issues, 2022)
Banjarmasin has a serious problem with unemployment. According to data from the Central Statistics Agency (BPS) of the City of Banjarmasin, the togetherness rate in the city of Banjarmasin rose by 0.78 percent between 2019 and 2021, with the COVID-19 pandemic playing a role. This forces individuals to adapt in order to continue facing life's challenges. One of the occupations chosen by the residents of Banjarmasin is that of the street performer. The concept used by street clowns in the city of Banjarmasin originated from the criteria of clowns themselves, which is that the clown is a supporting character by displaying interesting, funny, and endearing choreography and is now a clown who only sits while displaying facial expressions that beg for mercy from people. This study seeks to determine the motivations behind a person's decision to become a street clown and the significance of their emergence. The researcher employs Max Weber's Social Action theory and Abraham Maslow's Hierarchy of Needs theory in the analysis. This study employs a phenomenological research methodology. According to the findings of this study, someone becomes a street clown because one of their needs is unmet. Moreover, the public considers the presence of street clowns to be extremely disturbing. Since their practise has reached a crossroads. Therefore, it can endanger both motorists and clowns. Some consider street clowns beggars due to their practice of displaying a pitiful face to solicit money from the community. But the children had a different perspective; whatever face the clown saw was entertaining to them. This implies that the street clown has multiple meanings, depending on how the actor interprets the street clown's actions.